2007
DOI: 10.1177/0146167206292749
|View full text |Cite
|
Sign up to set email alerts
|

Learning What Feelings to Desire: Socialization of Ideal Affect Through Children's Storybooks

Abstract: Previous findings suggest that cultural factors influence ideal affect (i.e., the affective states that people ideally want to feel). Three studies tested the hypothesis that cultural differences in ideal affect emerge early in life and are acquired through exposure to storybooks. In Study 1, the authors established that consistent with previous findings, European American preschoolers preferred excited (vs. calm) states more (indexed by activity and smile preferences) and perceived excited (vs. calm) states a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
263
3
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(284 citation statements)
references
References 26 publications
13
263
3
5
Order By: Relevance
“…Tsai and colleagues examined the way in which children were differentially affected by these varying emotional displays within picture books. After exposure to a high-arousal picture book, American children were more likely to recognize ‚large smile‛ facial expressions as ‚happy‛ than after exposure to a lowarousal picture book (Tsai, Louie et al, 2007, Study 2).…”
Section: Arousal and Happiness: Cultural Valuationmentioning
confidence: 98%
See 1 more Smart Citation
“…Tsai and colleagues examined the way in which children were differentially affected by these varying emotional displays within picture books. After exposure to a high-arousal picture book, American children were more likely to recognize ‚large smile‛ facial expressions as ‚happy‛ than after exposure to a lowarousal picture book (Tsai, Louie et al, 2007, Study 2).…”
Section: Arousal and Happiness: Cultural Valuationmentioning
confidence: 98%
“…An analysis of bestseller picture books for children in the United States and in Taiwan shows best-selling U.S. picture books have protagonists with larger smiles than are present in Taiwanese bestsellers, and the actions those characters are depicted as taking are more reflective of ‚high-arousal‛ emotions than are the actions characters in the Taiwanese picture books are depicted as taking. Picture books in Taiwan and Japan show calmer images with the depiction of ‚low-arousal‛ emotions (Tsai, Louie, Chen, & Uchida, 2007; see also Oyama et al, 2008). Tsai and colleagues examined the way in which children were differentially affected by these varying emotional displays within picture books.…”
Section: Arousal and Happiness: Cultural Valuationmentioning
confidence: 99%
“…Several studies compared the emotions depicted in children's books in different cultures and found them to differ in meaningful ways [18][19][20]. For example, Tsai and her colleagues showed that best-selling children's storybooks in Taiwan portray more calm than excited smiles, in line with the cultural task of adjusting to others, whereas North American storybooks typically portray their main characters with excited rather than calm smiles, in line with the task of influencing environments [19,Study 2]. Thus, in each culture, children's books modeled the emotions conducive to the central cultural tasks.…”
Section: Cultural Construction Of Emotions: Processes At the Level Ofmentioning
confidence: 99%
“…First, through interacting with individuals of different cultural backgrounds, immigrants may be exposed to different models of emotional socialization and social structures that encourage or discourage the expression or discussion of emotion. Similarly, immigrants' use of cultural media (e.g., books, TV) may expose them to different models of emotional expression and influence individuals' preferences for affective states (Tsai, Louie, Chen, & Uchida, 2007). Moreover, the language immigrants use to express or discuss emotion may influence the intensity or frequency with which various emotions are expressed or discussed (see S. H. Chen, Kennedy, & Zhou, 2012, for a review).…”
Section: Cultural Influences On Parental Emotion Socializationmentioning
confidence: 99%